Platelet-Rich Plasma in Acute Achilles Tendon Ruptures: A Systematic Review and Meta-Analysis. Issue 4 (November 2022) - Abdolrazaghi, Sina; Akram, Nimra; Boksh, Khalis; Elbashir, Mohamed; Thomas, Owain; Divall, Pip; Mangwani, Jitendra
Category: Trauma; Sports Introduction/Purpose: Platelet Rich Plasma (PRP) is known to exert multi-directional biological effects favouring tendon healing. However, conclusions drawn by numerous studies on its clinical efficacy for acute Achilles tendon rupture are limited. We performed a systematic review and meta-analysis to investigate this and to compare to those without PRP treatment. Methods: The Cochrane Controlled Register of Trials, Pubmed, Medline and Embase were used and assessed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) criteria with the following search terms: ('plasma' OR 'platelet-rich' OR 'platelet-rich plasma' or 'PRP') AND ('Achilles tendon rupture/tear' OR' calcaneal tendon rupture/tear' OR 'tendo calcaneus rupture/tear'). Data pertaining to biomechanical outcomes (heel endurance test, isokinetic strength, calf- circumference and range of motion), patient-reported outcome measures (PROMs) and incidence of re-ruptures were extracted. Meta-analysis was performed for same outcomes measured in at least three studies. Pooled outcome data were analysed by random and fixed-effects models. Results: After abstract and full-text screening, 6 studies were included. In total there were 510 patients of which 256 had local PRP injection and 254 without. The average age was41.6 years, mean time from injury to treatment 5.9 days and mean follow-up at 61 weeks. Biomechanically, there was similar heel endurance, isokinetic strength, calf circumference and range of motion between both groups. In general, there were no differences in patient reported outcomes from all scoring systems used in the studies. Both groups returned to their pre-injured level at a similar time and there were no differences on the incidence of re- rupture (OR 1.13, 95% CI, 0.46 to 2.80, p = 0.79). Conclusion: PRP injections for acute Achilles tendon ruptures do not improve medium to long-term biomechanical and clinical outcomes. However, future studies incorporating the ideal application and biological composition of PRP are required to investigate its true clinical efficacy.